Proslavery and sectional thought in the early South, 1740-1829 : an anthology - Young, Jeffrey Robert (Book collections on Project MUSE., 2006)
Even then the theorists included in this anthology emphasized the extent to which southern slaveholders' claims to mastery were rooted in a Western moral tradition that reached back to antiquity.